Indicators of Environmental and Economic Problems Priority Arising from Energy Use in Food Manufacturing Sector in Realizing Sustainable Development Policy under Thai Environmental Law Framework - Sutthichaimethee, Pruethsan; Ariyasajjakorn, Danupon; Chatchorfa, Apinyar; Dockthaisong, Boonton; Naluang, Sthianrapab; Wongthongdee, Sirapatsorn; Thongjan, Nachatchaya (International Journal of Energy Economics and Policy, 2021)
This research was conducted to examine the true benefit of energy consumption within the scope of energy cost, as well as model a forecasting tool for energy cost in food manufacturing industry. It was limited to the analysis of true benefit of the consumption, energy cost, forward-and-backward relationship, and prediction of future energy cost during the next 10 years ranging from 2021 to 2030, and 20 years ranging from 2021 to 2040. The analysis was made possible via an application of ARIMAX model optimizing the input-output table of Thailand. As for the result, it reveals that the product of tobacco is found with the highest true value of benefit. While candy and sweets, sugar, breweries, corn, distilled spirit, slaughtering, milled rice, coffee and tea, and canned meat are respectively detected. In taking forward-and-backward relationship into account, a close monitoring is required for the sector of canned meat and milled rice, respectively. Since the developed model is confirmed for its validity, an optimization of RMSE, MAE, and MAPE measurement for 10 years (2021-2030) and 20 years (2021-2040) prediction of energy cost would result in the following outcomes; 1) a gradual increase of 41.86 percent is estimated for the energy cost by 2030 compared to 2021 per illustration in Model 1, and 2) energy cost is calculated at a steadily increased 70.79% by 2040 in comparison with 2021 per presentation in Model 2. Keywords: economic problem, environmental law, sustainability, Food Manufacturing sector, energy cost JEL Classifications: P28, Q42, Q43, Q47, Q48 DOI: https://doi.org/10.32479/ijeep.11515